Short-term Training Programs for Immigrants: Do Effects Differ from Natives and Why? - Stephan L. Thomsen; Alisher Aldashev; Thomas Walter (Verein für Socialpolitik, 2010)
We evaluate the effects of different short-term training programs on the employment chances of immigrant and native welfare recipients in Germany. In particular, we investigate whether program effects differ between both groups and what might cause these potential differences. In a first step, we evaluate program effects separately for immigrants and natives using propensity score matching estimators. To explain potential differences in effects between the groups, we suggest and apply a decomposition method based on the matching procedure that allows identification of differences due to observable characteristics and differences related to an immigrant fixed effect in a second step.
Keywords: I38; C14; J61; 330; Immigrants; short-term training programs; evaluation; decomposition; matching; Germany